Method for resource utilization of aluminum ash
Through a full-process comprehensive resource utilization process combining dry and wet methods, the aluminum ash slag is processed in multiple steps, solving the problems of land resource waste and environmental pollution in aluminum ash treatment, and achieving efficient resource utilization of valuable elements in aluminum ash slag.
Patent Information
- Application Number
- CN202311414383.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-10-27
AI Technical Summary
The existing aluminum ash slag treatment technology has serious waste of land resources, and the removal effect of fluoride and heavy metals is not ideal, resulting in environmental pollution.
The full-process comprehensive resource utilization process combining dry and wet methods is adopted to perform multi-step treatments such as crushing, grinding, screening, heating and melting, oxidation treatment, solid sulfur reaction, flocculation and settlement and concentration treatment to achieve the resource utilization of valuable elements in the aluminum ash slag.
The basic resource utilization of valuable elements in aluminum ash slag has been achieved, the process is simple, energy-saving and environmentally friendly, and the resource recovery rate is high, avoiding waste of land resources and environmental pollution.
Smart Images

Figure CN119897337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to resource treatment of aluminum ash slag, and in particular to a method for resource utilization of aluminum ash slag, belonging to the technical field of resource treatment of aluminum ash slag. Background Art
[0002] my country's aluminum smelting and processing industry is huge. In 2019, the output of primary aluminum was 35 million tons, the output of aluminum processed products was 41 million tons, and the output of recycled aluminum was 6 million tons. The aluminum industry is a typical high-energy consumption and high-pollution industry. A large amount of solid waste, especially hazardous waste, is generated during the production and processing process, which is an obstacle to the green development of the aluminum industry. Aluminum ash slag is a solid waste generated during the process of primary aluminum smelting, aluminum alloy processing, and aluminum recycling. Aluminum ash slag contains more aluminum, alumina, and chloride salts, and also contains a small amount of fluoride, silicon and other heavy metals. In addition, due to the different origins of the original ore, the composition of the aluminum ash slag obtained after smelting using the same process fluctuates greatly. In addition, during the high-temperature smelting process, liquid aluminum reacts with nitrogen in the air to form aluminum nitride. The fine aluminum nitride is black. After cooling, the aluminum nitride (AlN) in the aluminum ash easily reacts with water in the air to produce ammonia. Therefore, the aluminum ash slag has a foul odor and is in the form of black powder. It is mixed with a large number of large particles of metal aluminum flakes (grains) and salts, and may contain trace amounts of Al4C3 and Al2S3.
[0003] Fluoride, heavy metals and other toxic substances contained in aluminum ash are also highly harmful to the environment. If not properly handled, they will cause soil, groundwater and air pollution. Fluoride pollution can affect plant photosynthesis and respiration, and damage human bones, teeth and central nervous system.
[0004] At present, most of the aluminum ash slag treatment is to build storage yards, which not only wastes land resources but also causes environmental pollution. Therefore, it is necessary to develop more efficient aluminum ash slag treatment technology. Summary of the invention
[0005] In view of the problems of serious waste of land resources, unsatisfactory removal of fluoride and heavy metals and environmental pollution caused by aluminum ash slag treatment technology in the prior art, the present invention provides a method for resource utilization of aluminum ash slag. The present invention combines dry method with wet method and cleverly designs the process of comprehensive resource utilization of the whole process, and basically achieves the purpose of full resource utilization of valuable elements in aluminum ash slag. The process is simple, energy-saving and environmentally friendly, and has a high resource recovery rate.
[0006] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are specifically described as follows:
[0007] A method for resource utilization of aluminum ash slag, the method comprising the following steps:
[0008] 1) The aluminum ash slag is first crushed and ground, and then sieved to obtain coarse aluminum ash slag and fine aluminum ash slag.
[0009] 2) The crude aluminum ash is heated and melted into a molten liquid, and the molten liquid is cooled after removing the scum. The collected scum is returned to the aluminum ash in step 1).
[0010] 3) Adding a fluorine-fixing agent and a catalyst to the fine aluminum ash to mix and obtain a mixture, and sieving the mixture to obtain a coarse mixture and a fine mixture. The coarse mixture is mixed with the coarse aluminum ash to perform step 2), and the fine mixture is processed in the next step.
[0011] 4) After the fine mixture is mixed evenly, it is subjected to oxidation treatment, and then subjected to a sulfur fixation reaction, and after the reaction is completed, a sulfur fixation material is obtained.
[0012] 5) The sulfur-fixing material is mixed with a flocculant and water for sedimentation treatment to obtain sediment residue and sediment liquid. The sediment residue is dried and used as a concrete raw material, and the sediment liquid is processed in the next step.
[0013] 6) The sedimentation liquid is concentrated, and the pH of the concentrated liquid is adjusted to perform an aluminum precipitation reaction. After the precipitation is completed, it is filtered, and the filter residue is dried to obtain aluminum hydroxide powder. The filtrate is further concentrated to obtain a refining agent raw material.
[0014] Preferably, the method further comprises:
[0015] 7) Collect and merge the waste gas generated in step 3), step 4) and step 5) to perform elution to obtain ammonia water. The evaporated water generated by the two concentration treatments in step 6) is recycled to step 5) for use.
[0016] Preferably, step 3), step 4) and step 5) are all carried out under an atmosphere protected by a protective gas. Preferably, the protective gas is one of nitrogen, helium, neon and argon, preferably nitrogen.
[0017] Preferably, the aluminum ash slag is one or more of aluminum ash slag I, aluminum ash slag II, and aluminum ash slag III. Preferably, it is a mixed aluminum ash slag in which aluminum ash slag I, aluminum ash slag II, and aluminum ash slag III are mixed in a mass ratio of 1-3:1-2:1.5-3, and preferably in a mass ratio of 1.6-2:1.1-1.5:2-2.5. Wherein:
[0018] Aluminum ash slag I includes: Al content 39% to 42%, Ca content 2% to 3.5%, Mg content 0% to 1.2%, F content 1% to 3%, Cl content 10% to 12%, S content 0.5% to 0.8%, N content 1% to 5%;
[0019] Aluminum ash slag II includes: Al content 20% to 32%, Ca content 2.5% to 4.5%, Mg content 2.2% to 4%, F content 1.5% to 2%, Cl content 6% to 9%, S content 0.2% to 0.5%, N content 2% to 4%;
[0020] Aluminum ash slag III includes: Al content 40% to 48%, Ca content 0% to 1%, Mg content 1.8% to 3.8%, F content 2% to 3%, Cl content 1% to 5%, S content 0.4% to 0.5%, and N content 3% to 4%.
[0021] Preferably, in step 1), the particle size of the coarse aluminum ash is 1.8-5 mm, preferably 2-4 mm, for example, 1.8 mm, 1.9 mm, 2 mm, 2.1 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 3 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4 mm, 4.2 mm, 4.5 mm, 4.8 mm, 5 mm. The particle size of the fine aluminum ash is 0.5-1.9 mm, preferably 1-1.7 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, etc.
[0022] Preferably, in step 3), the particle size of the coarse mixture is 1.5-5 mm, preferably 2-4.5 mm, for example, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2 mm, 2.2 mm, 2.4 mm, 2.6 mm, 2.8 mm, 3 mm, 3.2 mm, 3.5 mm, 3.8 mm, 4 mm, 4.2 mm, 4.5 mm, 4.8 mm, 5 mm. The particle size of the fine mixture is 0.5-1.9 mm, preferably 1-1.4 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm.
[0023] Preferably, in step 3), the fluorine-fixing agent is calcium acetate and / or calcium-magnesium acetate, preferably a mixture of calcium acetate and calcium-magnesium acetate, the mixing mass ratio of the two being 1:1.5-5, preferably 1:2-3.
[0024] Preferably, in step 3), the catalyst is a mixture of polymethyl acrylate and calcium oxide. Preferably, the mixing mass ratio of polymethyl acrylate to calcium oxide is 1:3.5-8, preferably 1:4-5.5.
[0025] Preferably, the amount of the fluorine-fixing agent added is 2-8% of the mass of the fine aluminum ash, preferably 3-5%, for example, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%. The amount of the catalyst added is 3-10% of the mass of the fine aluminum ash, preferably 4-8%, for example, 3%, 3.2%, .4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%.
[0026] Preferably, in step 4), the oxidation treatment is to introduce an oxidizing gas into the fine mixture to carry out an oxidation reaction. The oxidizing gas is oxygen or ozone.
[0027] Preferably, in step 4), the desulfurization reaction is specifically: introducing carbon dioxide into the oxidized fine mixture.
[0028] Preferably, the amount of carbon dioxide introduced is 10 to 30 m 3 / h, preferably 15 to 25 m 3 / h. The reaction time is 30 to 120 min, preferably 40 to 100 min.
[0029] Preferably, in step 5), the flocculant is nonionic polyacrylamide. The mixing mass ratio of the sulfur-fixing material, the flocculant, and water is 50-58:5-9:40-50, preferably 52-56:6-8:42-48. The sedimentation treatment time is 30-120 minutes, preferably 40-100 minutes.
[0030] Preferably, in step 6), the concentration multiple of the sedimentation liquid is 2 to 7 times, preferably 2.5 to 5 times.
[0031] Preferably, the pH of the concentrated solution is adjusted to 7-8.5, preferably 7.5-8.2.
[0032] Preferably, the filtrate is concentrated 2 to 6 times, preferably 3 to 5 times.
[0033] In the prior art, aluminum ash slag is mostly treated by open-air storage, or simply by targeted recycling of some resources (such as aluminum resources, iron, silicon, etc.), but the recycling effect is not ideal, and there are still problems of environmental pollution caused by secondary residues, waste gas, etc. Through research, the present invention specifically proposes a treatment process that can achieve the purpose of basically complete resource utilization of valuable elements in aluminum ash slag. The process is simple, energy-saving and environmentally friendly, and has a high resource recovery rate.
[0034] In the present invention, most of the metal aluminum in the aluminum ash is first recovered by mechanical dry separation. The aluminum ash is mainly crushed (for example, crushed to a particle size of 5 to 10 mm) to achieve preliminary refinement of the aluminum ash, and then the aluminum ash after preliminary refinement is further refined by ball milling (for example, ball milling to a particle size of 1 to 2 mm). After two refinements, the metal aluminum coated and included in the aluminum ash is released as much as possible, and the coarse and fine particles are separated by screening, and the coarse particles with a large metal aluminum content are smelted at high temperature, and the scum converted from impurities is removed and cooled and cast to obtain high-quality aluminum ingots. That is, the separation of metal aluminum from impurities is initially achieved through mechanical and physical processes such as crushing, ball milling, and screening (equivalent to stripping and enriching metal aluminum from the slag phase), and then the impurities mixed in the metal aluminum are removed in reverse by smelting (the scum also contains aluminum, so it is mixed and circulated with other aluminum ash for the aforementioned treatment), and finally a high-quality metal aluminum ingot is obtained.
[0035] In the present invention, the fine particle material (i.e., fine aluminum ash) separated by mechanical dry method contains more impurities and aluminum, and part of the aluminum element exists in the form of stable compounds. A specific fluorine-fixing agent and a catalyst are added to the fine particle material under the screen to fix the fluorine in the fine particle material and promote the consolidation of the aluminum-containing powder. That is, under the joint action of the fluorine-fixing agent and the catalyst, part of the aluminum-containing powder in the fine particle material is solidified into large particles, and the large particles have a high aluminum content. Therefore, high-frequency vibration screening is continued, and the large particles solidified by the aluminum-containing powder are returned for high-temperature smelting to further achieve the separation and recovery of metallic aluminum and impurities.
[0036] In the present invention, the fluorine-fixing agent is calcium acetate and / or calcium-magnesium acetate, preferably a mixture of calcium acetate and calcium-magnesium acetate, and the mixing mass ratio of the two is 1:1.5-5 (preferably 1:2-3). The catalyst is a mixture of polymethyl acrylate and calcium oxide, and the mixing mass ratio of the two is 1:3.5-8 (preferably 1:4-5). During the reaction process, the catalyst can promote the reaction and also promote the consolidation of aluminum-containing powder. Too large or too small a mixing ratio of polymethyl acrylate and calcium oxide will reduce the catalytic effect.
[0037] It should be noted that the collected high-frequency vibration screening undersize materials need to be continuously stirred and reacted for a period of time in order to achieve deep fluorine fixation. The fluorine content in fine particles is high and generally needs to be treated first, while the sulfur content is low and can be treated later. Fluorine fixation is to combine fluorine ions with calcium ions to form calcium fluoride (entering the concrete raw materials).
[0038] In the present invention, the aluminum ash slag also contains a certain amount of sulfur element. An oxidizing gas is introduced into the material under the high-frequency vibration screening and stirred to carry out an oxidation reaction on the sulfur element, and then carbon dioxide is introduced and stirred continuously to achieve sulfur fixation. That is, an acidic environment is generated by introducing carbon dioxide into the material, and under the high-intensity oxidation of ozone, the sulfide in the material forms a calcium sulfate stabilizer in the acidic environment to achieve sulfur fixation.
[0039] In the present invention, the material after the sulfur fixation reaction is mixed with a flocculant (such as nonionic polyacrylamide) and water in a certain proportion (for example, the ratio of sulfur fixation material, flocculant and water is 50%-58%: 5%-9%: 40%-45%), and the micro-particles generated in the material after the sulfur fixation reaction and the micro-particles generated in the above steps are condensed, which can promote the sinking of the condensate and the clarification of the liquid. After the carbon dioxide is introduced and water is added, an acidic environment is formed, so that most of the aluminum-containing substances are dissolved, and the aluminum-free materials form precipitates under the action of the flocculant to facilitate removal.
[0040] In the present invention, the material after the solid sulfur is precipitated is filtered to obtain a filter residue (the composition of the filter residue is relatively complex, with carbonates and a small amount of sulfates, and the fixed fluorine also enters the filter residue. As a concrete raw material, the concrete raw material can be used to make low-strength concrete, and the filter residue resource utilization can be realized) and a filtrate. The filter residue is dried to obtain the concrete raw material. The filtrate is concentrated to obtain a concentrated salt solution and part of the distilled water, and the distilled water can be recycled. The pH of the concentrated salt solution is adjusted while the concentrated salt solution is crystallized, and the metal impurities other than aluminum in the concentrated salt solution can continue to be dissolved, and aluminum hydroxide precipitation is precipitated to improve the purity of aluminum hydroxide. After the crystallization precipitation is completed, a second filtration is performed to obtain aluminum hydroxide wet powder and a second filtrate, and the aluminum hydroxide wet powder is dried to obtain aluminum hydroxide powder. At the same time, the second filtrate is continuously evaporated and concentrated to obtain a refining agent raw material. The refining agent raw material is a powdery or granular flux composed of a variety of inorganic salts (that is, the filtrate is concentrated to obtain a variety of inorganic salts). Its purpose is: in the refining of aluminum, it can be used to remove hydrogen and floating oxide slag inside the aluminum liquid.
[0041] In the present invention, ammonia is generated in the processes of fluorine solidification and sulfur solidification precipitation, so a protective gas (such as nitrogen) is introduced during these processes to create a protective atmosphere, and the generated ammonia is taken out and sent to a special leaching device to perform leaching, absorption and separation of the ammonia carried out to obtain ammonia water, thereby realizing the resource recovery of harmful waste gas. The protective gas after removing the ammonia can also be recycled.
[0042] In the present invention, the aluminum ash slag is a mixed aluminum ash slag obtained by mixing aluminum ash slags with significantly different components. In the existing production process of raw aluminum, due to the different sources of raw ore, the component content of the aluminum ash slag finally obtained is significantly different. Some aluminum ash slags have a higher chlorine content (such as raw ore produced by coastal factories or coastal mining areas), while some aluminum ash slags have a higher calcium or magnesium content. Due to the differences in the fluctuations in the content of recyclable elements in aluminum ash slag, targeted considerations are inevitably required in the process of fully resource-based recycling and treatment of them. Therefore, it is impossible to use the same set of treatment processes to match aluminum ash slags with a variety of different component contents. Establishing a special resource production line for each type of aluminum ash slag has the problems of excessive investment cost and difficulty in full resource recycling. It does not have economic effects and cannot meet the needs of economic enterprises. The present invention mixes three special components of aluminum ash slag and studies and develops a set of processes for the full resource utilization of mixed aluminum ash slag. On the one hand, it realizes the purpose of recycling multiple aluminum ash slags with the same resource utilization process; on the other hand, aluminum ash slags containing different components complement each other, which can promote and improve the quality of resource products recycled at all levels, and truly and efficiently realize the full resource utilization of aluminum ash slag. All aluminum ash slag is recycled: metal aluminum sheets are recycled; ammonia water is formed into products for sale; high-aluminum materials are sold to alumina production plants, floor tile plants or water purifier plants; high-salt water is used to extract refining agent raw materials to form products for sale; concrete raw materials are used for concrete preparation.
[0043] Compared with the prior art, the present invention has the following beneficial technical effects:
[0044] 1: The aluminum ash slag resource processing process of the present invention does not need to build a large number of storage yards, saves land resources, and does not cause environmental pollution. It belongs to a more efficient aluminum ash slag processing technology, realizes the efficient and maximum resource utilization of existing aluminum ash slag, is cleaner and has a high recovery rate.
[0045] 2: The present invention adopts dry-wet separation to extract aluminum flakes. First, the dry method is used to extract most of the aluminum in the aluminum ash, so that the aluminum can be collected early. Then the wet method is used to further extract the aluminum. The recovery rate of aluminum flakes is high (up to about 95%). The present invention also adopts wet mechanochemical fluorine fixation and deamination, which is highly efficient, environmentally friendly, completely processed, and has low operating costs.
[0046] 3: The process of the present invention is ingenious, the process is energy-saving and environmentally friendly, the resource recovery rate is high, the various products obtained are of good quality (high grade, good chemical composition) and high strength, the process also achieves ultra-low emissions, and the engineering economic benefits are excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The present invention is a flowchart of the process of the aluminum ash slag resource utilization method.
[0048] Figure 2 This is a complete process flow chart of the aluminum ash slag resource utilization method of the present invention. DETAILED DESCRIPTION
[0049] In order to further elaborate on the specific scheme of the present invention, the technical scheme claimed for protection of the present invention will be described below in conjunction with the drawings and examples. The following examples are only preferred implementation schemes of the present invention and should not be regarded as limiting the scope of protection claimed for the present invention.
[0050] Example 1
[0051] A method for resource utilization of aluminum ash slag, the method comprising the following steps:
[0052] 1) Firstly, the aluminum ash slag is crushed and ground, and then sieved to obtain coarse aluminum ash slag and fine aluminum ash slag;
[0053] 2) heating and melting the crude aluminum ash into a molten liquid, removing the scum from the molten liquid and cooling it to obtain an aluminum ingot; returning the collected scum to the aluminum ash in step 1);
[0054] 3) adding a fluorine-fixing agent and a catalyst to the fine aluminum ash to mix and obtain a mixture, and sieving the mixture to obtain a coarse mixture and a fine mixture; the coarse mixture is mixed with the coarse aluminum ash to perform step 2), and the fine mixture is processed in the next step;
[0055] 4) After the fine mixture is mixed evenly, it is subjected to oxidation treatment, and then subjected to a sulfur fixation reaction, and after the reaction is completed, a sulfur fixation material is obtained;
[0056] 5) Mixing the solid sulfur material with a flocculant and water for sedimentation treatment to obtain sediment residue and sediment liquid; drying the sediment residue as a concrete raw material, and subjecting the sediment liquid to the next step of treatment;
[0057] 6) The sedimentation liquid is concentrated, and the pH of the concentrated liquid is adjusted to perform an aluminum precipitation reaction. After the precipitation is completed, it is filtered, and the filter residue is dried to obtain aluminum hydroxide powder. The filtrate is further concentrated to obtain a refining agent raw material.
[0058] Example 2
[0059] Repeat Example 1, except that the method further comprises:
[0060] 7) The waste gas generated during step 3), step 4) and step 5) is collected and combined for elution to obtain ammonia water; the evaporated water generated by the two concentration treatments in step 6) is recycled to step 5) for use.
[0061] Example 3
[0062] Example 2 was repeated, except that steps 3), 4) and 5) were all carried out under a nitrogen atmosphere.
[0063] The aluminum ash slag is a mixed aluminum ash slag obtained by mixing aluminum ash slag I, aluminum ash slag II, and aluminum ash slag III in a mass ratio of 1.8:1.3:2.4; wherein:
[0064] The chemical composition of aluminum ash slag I is: Al content 39% to 42%, Si content 2% to 5%, Fe content 1% to 2%, Ca content 2% to 3.5%, Mg content 0% to 1.2%, F content 1% to 3%, Na content 2% to 7%, Cl content 10% to 12%, S content 0.5% to 0.8%, K content 0.2% to 0.4%, N content 1% to 5%;
[0065] The chemical composition of aluminum ash slag II is: Al content 20% to 32%, Si content 1% to 4%, Fe content 1% to 1.5%, Ca content 2.5% to 4.5%, Mg content 2.2% to 4%, F content 1.5% to 2%, Na content 3% to 5%, Cl content 6% to 9%, S content 0.2% to 0.5%, K content 0.3% to 0.45%, N content 2% to 4%;
[0066] The chemical composition of aluminum ash slag III is: Al content 40% to 48%, Si content 3% to 4%, Fe content 0.5% to 1.8%, Ca content 0% to 1%, Mg content 1.8% to 3.8%, F content 2% to 3%, Na content 4% to 6%, Cl content 1% to 5%, S content 0.4% to 0.5%, K content 0.1% to 0.2%, and N content 3% to 4%.
[0067] In step 1), the particle size of the coarse aluminum ash slag is 2 to 5 mm; the particle size of the fine aluminum ash slag is 1 to 1.6 mm.
[0068] In step 3), the particle size of the coarse mixture is 1.6-5 mm; the particle size of the fine mixture is 1-1.5 mm. The fluorine-fixing agent is calcium acetate; the catalyst is a mixture of polymethyl acrylate and calcium oxide, and the mixing mass ratio of polymethyl acrylate to calcium oxide is 1:4.5; the amount of the fluorine-fixing agent added is 4% of the mass of the fine aluminum ash slag; the amount of the catalyst added is 7.5% of the mass of the fine aluminum ash slag.
[0069] In step 4), the oxidation treatment is to introduce ozone into the fine mixture for oxidation reaction; in step 4), the amount of carbon dioxide introduced is 20m 3 / h; reaction time is 80min.
[0070] In step 5), the flocculant is nonionic polyacrylamide; the mixing mass ratio of the sulfur-fixing material, the flocculant and water is 52:7:45; and the sedimentation treatment time is 70 minutes.
[0071] In step 6), the concentration multiple of the sedimentation liquid is 5 times; the pH of the concentrated liquid is adjusted to 7-8.5; and the concentration multiple of the filtrate is 4 times.
[0072] Example 4
[0073] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was calcium magnesium acetate.
[0074] Example 5
[0075] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:1.
[0076] Example 6
[0077] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:1.5.
[0078] Example 7
[0079] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:2.
[0080] Example 8
[0081] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:2.5.
[0082] Example 9
[0083] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:3.
[0084] Example 10
[0085] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:3.5.
[0086] Embodiment 11
[0087] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:4.5.
[0088] Example 12
[0089] Example 3 was repeated, except that in step 3), the fluorine-fixing agent was a mixture of calcium acetate and calcium magnesium acetate, and the mixing mass ratio of the two was 1:5.5.
[0090] Example 13
[0091] Example 8 was repeated, except that in step 3), the mixing mass ratio of polymethyl acrylate to calcium oxide was 1:3.5.
[0092] Embodiment 14
[0093] Example 8 was repeated, except that in step 3), the mixing mass ratio of polymethyl acrylate to calcium oxide was 1:4.
[0094] Embodiment 15
[0095] Example 8 was repeated, except that in step 3), the mixing mass ratio of polymethyl acrylate to calcium oxide was 1:5.
[0096] Example 16
[0097] Example 8 was repeated, except that the mixing mass ratio of the first aluminum ash slag, the second aluminum ash slag, and the third aluminum ash slag was 1.6:1.1:2.5.
[0098] Embodiment 17
[0099] Example 8 was repeated, except that the mixing mass ratio of the first aluminum ash slag, the second aluminum ash slag, and the third aluminum ash slag was 2:1.5:2.
[0100] Embodiment 18
[0101] Example 8 was repeated, except that the aluminum ash slag was only the first type of aluminum ash slag.
[0102] Embodiment 19
[0103] Example 8 was repeated, except that the aluminum slag was only the second type of aluminum slag.
[0104] Embodiment 20
[0105] Example 8 was repeated, except that the aluminum ash slag was only the third type of aluminum ash slag.
[0106] Embodiment 21
[0107] Example 8 was repeated, except that the aluminum ash slag was only the first aluminum ash slag and the second aluminum ash slag.
[0108] Embodiment 22
[0109] Example 8 was repeated, except that the aluminum ash slag was only the first aluminum ash slag and the third aluminum ash slag.
[0110] Embodiment 23
[0111] Example 8 was repeated, except that the aluminum ash slag was only the second aluminum ash slag and the third aluminum ash slag.
[0112] Comparative Example 1
[0113] Example 8 was repeated except that no fluorine-fixing agent was used in step 3).
[0114] Comparative Example 2
[0115] Example 8 was repeated except that no catalyst was used in step 3) and the fluorine-fixing agent was only calcium acetate.
[0116] Comparative Example 3
[0117] Example 8 was repeated except that no catalyst was used in step 3) and the fluorine-fixing agent was only calcium magnesium acetate.
[0118] Comparative Example 4
[0119] Example 8 was repeated except that no catalyst was used in step 3).
[0120] Main process parameters and effect comparison table:
[0121]
[0122]
Claims
1. A method for resource utilization of aluminum ash slag, characterized in that: The method comprises the following steps: 1) Firstly, the aluminum ash slag is crushed and ground, and then sieved to obtain coarse aluminum ash slag and fine aluminum ash slag; 2) heating and melting the crude aluminum ash into a molten liquid, removing the scum from the molten liquid and cooling it to obtain an aluminum ingot; returning the collected scum to the aluminum ash in step 1); 3) adding a fluorine-fixing agent and a catalyst to the fine aluminum ash to mix and obtain a mixture, and sieving the mixture to obtain a coarse mixture and a fine mixture; the coarse mixture is mixed with the coarse aluminum ash to perform step 2), and the fine mixture is processed in the next step; 4) After the fine mixture is mixed evenly, it is subjected to oxidation treatment, and then subjected to a sulfur fixation reaction, and after the reaction is completed, a sulfur fixation material is obtained; 5) Mixing the solid sulfur material with a flocculant and water for sedimentation treatment to obtain sediment residue and sediment liquid; drying the sediment residue as a concrete raw material, and subjecting the sediment liquid to the next step of treatment; 6) The sedimentation liquid is concentrated, and the pH of the concentrated liquid is adjusted to perform an aluminum precipitation reaction. After the precipitation is completed, it is filtered, and the filter residue is dried to obtain aluminum hydroxide powder. The filtrate is further concentrated to obtain a refining agent raw material.
2. The method according to claim 1, characterized in that: The method further includes: 7) The waste gas generated during step 3), step 4) and step 5) is collected and combined for elution to obtain ammonia water; the evaporated water generated by the two concentration treatments in step 6) is recycled to step 5) for use.
3. The method according to claim 1 or 2, characterized in that: Step 3), step 4) and step 5) are all carried out under an atmosphere of protective gas; preferably, the protective gas is one of nitrogen, helium, neon and argon, preferably nitrogen.
4. The method according to any one of claims 1 to 3, characterized in that: The aluminum ash slag is one or more of aluminum ash slag I, aluminum ash slag II, and aluminum ash slag III; preferably, aluminum ash slag I, aluminum ash slag II, and aluminum ash slag III are mixed in a mass ratio of 1-3:1-2:1.5-3, preferably 1.6-2:1.1-1.5:2-2.5; wherein: Aluminum ash slag I includes: Al content 39% to 42%, Ca content 2% to 3.5%, Mg content 0% to 1.2%, F content 1% to 3%, Cl content 10% to 12%, S content 0.5% to 0.8%, N content 1% to 5%; Aluminum ash slag II includes: Al content 20% to 32%, Ca content 2.5% to 4.5%, Mg content 2.2% to 4%, F content 1.5% to 2%, Cl content 6% to 9%, S content 0.2% to 0.5%, N content 2% to 4%; Aluminum ash slag III includes: Al content 40% to 48%, Ca content 0% to 1%, Mg content 1.8% to 3.8%, F content 2% to 3%, Cl content 1% to 5%, S content 0.4% to 0.5%, and N content 3% to 4%.
5. The method according to any one of claims 1 to 4, characterized in that: In step 1), the particle size of the coarse aluminum ash is 1.8 to 5 mm, preferably 2 to 4 mm; the particle size of the fine aluminum ash is 0.5 to 1.9 mm, preferably 1 to 1.7 mm; and / or In step 3), the particle size of the coarse mixture is 1.5 to 5 mm, preferably 2 to 4.5 mm; the particle size of the fine mixture is 0.5 to 1.9 mm, preferably 1 to 1.4 mm.
6. The method according to any one of claims 1 to 5, characterized in that: In step 3), the fluorine-fixing agent is calcium acetate and / or calcium-magnesium acetate; preferably a mixture of calcium acetate and calcium-magnesium acetate, the mixing mass ratio of the two is 1:1.5-5, preferably 1:2-3; and / or In step 3), the catalyst is a mixture of polymethyl acrylate and calcium oxide; preferably, the mixing mass ratio of polymethyl acrylate to calcium oxide is 1:3.5-8, preferably 1:4-5; Preferably, the amount of the fluorine-fixing agent added is 2-8% of the mass of the fine aluminum ash slag, preferably 3-5%; the amount of the catalyst added is 3-10% of the mass of the fine aluminum ash slag, preferably 4-8%.
7. The method according to any one of claims 1 to 6, characterized in that: In step 4), the oxidation treatment is to introduce an oxidizing gas into the fine mixture to carry out an oxidation reaction; the oxidizing gas is oxygen or ozone.
8. The method according to any one of claims 1 to 7, characterized in that: In step 4), the desulfurization reaction is specifically as follows: carbon dioxide is introduced into the oxidized fine mixture; preferably, the amount of carbon dioxide introduced is 10 to 30 m 3 / h, preferably 15 to 25 m 3 / h; the reaction time is 30 to 120 min, preferably 40 to 100 min.
9. The method according to any one of claims 1 to 8, characterized in that: In step 5), the flocculant is nonionic polyacrylamide; the mixing mass ratio of the sulfur-fixing material, the flocculant and water is 50-58:5-9:40-50, preferably 52-56:6-8:42-48; the sedimentation treatment time is 30-120 minutes, preferably 40-100 minutes.
10. The method according to any one of claims 1 to 9, characterized in that: In step 6), the concentration multiple of the sedimentation liquid is 2 to 7 times, preferably 2.5 to 5 times; and / or Adjusting the pH of the concentrated solution specifically includes adjusting the pH of the concentrated solution to 7-8.5, preferably 7.5-8.2; and / or The filtrate is concentrated 2 to 6 times, preferably 3 to 5 times.
Citation Information
Patent Citations
Method for preparing aluminum oxide from aluminiferous material
CN101734698A
Aluminum ash harmless recycling comprehensive treatment system and method
CN109647853A
Harmless treatment method for secondary aluminum ash
CN114273382A
Method for separating iron, silicon, gallium, aluminum and calcium from fly ash
CN116790887A
Process for the recovery of aluminium from drosses
EP0167789A1